PERANGKAP KAPITALISME DALAM ADOPSI INTERNATIONAL FINANCIAL REPORTING STANDARDS (IFRS) - Yeterina Widi Nugrahanti (Dinamika Akuntansi Keuangan dan Perbankan, 2016)
Capitalism is believed to bring profit to the owners of capital and encourage economic growth, but the bad impact it generates for the wider community is also more so that capitalism creates a seemingly endless snare. Accounting as part of the economy also can not be separated from capitalism. This article aims to explain the traps of capitalism inherent in the adoption of the International Financial Reporting Standard (IFRS). The traps of capitalism inherent in the adoption of IFRS include (a) increasing opportunities for foreign investors to exploit the natural resources and human resources in Indonesia, (b) the opening of opportunities for the capitalist economic system to replace the family economy system mandated by the Constitution 1945, (c) fair value accounting in IFRS provides an instrument for profit accumulation greed, (d) IFRS adoption encourages Indonesia to engage in global markets so as to facilitate 'flow of things capitalism', which affects the accumulation of money (profit) as the sole Goals and other "value" waivers, including moral values. Efforts to compensate for the trap of capitalism in IFRS adoption can be an increase in the ethics of accountants' learning adapted to the ideology of Indonesia and the value of the Godhead, the development of business processes and accounting practices based on religious values, and the development of critical accounting discourse as a means of awareness of the adverse effects of capitalism. Keywords: trap of capitalism, accounting, adoption of IFRS